Identifikasi Unsur dan Konsep Geometris pada Rumah Adat Prai Ijing Sumba Barat - Dorothea Novia Ludo Lubur (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Ethnomathematics is a field of science that studies the relationship between mathematics and culture. This research aims to: find out the form of geometry contained in the Prai Ijing traditional house and find out the utilisation of geometry aspects in schools. The object of this research is the culture that develops in the community in the village of Prai Ijing. The type of research used in this study uses a qualitative descriptive approach. In particular, this study uses an ethnographic research approach. The results obtained are the form of geometry found in traditional houses are isosceles trapezoids, isosceles triangles, blocks, and pyramids and the benefits of geometry aspects in schools are in mathematics lessons there is a subject matter that is geometry